2018
DOI: 10.1002/jmv.25289
|View full text |Cite
|
Sign up to set email alerts
|

Role of phenol red in the stabilization of the Sabin type 2 inactivated polio vaccine at various pH values

Abstract: To analyze the effects of phenol red at various pH values on the Sabin type 2 inactivated polio vaccine (sIPV2), several biophysical techniques were used to evaluate the particle size and capsid protein for conformation. sIPV2's size was assessed via transmission electron microscopy and dynamic light scattering. The effects of various pH values (from 4.0 to 7.0) on the biophysical characters of sIPV2 particles in solution were determined by dynamic light scattering and zeta potential. The results clearly indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have found that sIPV antigens were spherical particles of about 30∼40 nm [ 20 , 21 ]. When aluminum adjuvant combined with Hib or sIPV, the particle size of all vaccines increased compared with the corresponding aluminum adjuvant.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that sIPV antigens were spherical particles of about 30∼40 nm [ 20 , 21 ]. When aluminum adjuvant combined with Hib or sIPV, the particle size of all vaccines increased compared with the corresponding aluminum adjuvant.…”
Section: Resultsmentioning
confidence: 99%
“…Phenol red, a colorimetric dye used in tissue culture media to monitor pH during fermentation, had a significant stabilizing impact on the sIPV2 at lower pH. 47 Freezing, caused either intentionally by storage at −20°C or inadvertently by improper cold storage, resulted in a significant reduction in D-antigen content. 48 For example, the D-antigen content measured in vaccine samples stored at −20°C for 1-day, or 1-week, or after mimicking improper cold storage for 3 freeze–thaw cycles was significantly reduced.…”
Section: Analytical and Preformulation Characterization Of Polio Vacc...mentioning
confidence: 99%